A Chronological Study on Grapevine Leafroll-Associated Virus 2 in Australia - Nuredin Habili; Qi Wu; Amy Rinaldo; Fiona Constable (Viruses, 2023)
Grapevine leafroll disease affects the health status of grapevines worldwide. Most studies in Australia have focused on grapevine leafroll-associated viruses 1 and 3, while little attention has been given to other leafroll virus types, in particular, grapevine leafroll-associated virus 2 (GLRaV-2). A chronological record of the temporal occurrence of GLRaV-2 in Australia since 2001 is reported. From a total of 11,257 samples, 313 tested positive, with an overall incidence of 2.7%. This virus has been detected in 18 grapevine varieties and Vitis rootstocks in different regions of Australia. Most varieties were symptomless on their own roots, while Chardonnay showed a decline in virus-sensitive rootstocks. An isolate of GLRaV-2, on own-rooted Vitis vinifera cv. Grenache, clone SA137, was associated with severe leafroll symptoms after veraison with abnormal leaf necrosis. The metagenomic sequencing results of the virus in two plants of this variety confirmed the presence of GLRaV-2, as well as two inert viruses, grapevine rupestris stem pitting-associated virus (GRSPaV) and grapevine rupestris vein feathering virus (GRVFV). No other leafroll-associated viruses were detected. Among the viroids, hop stunt viroid and grapevine yellow speckle viroid 1 were detected. Of the six phylogenetic groups identified in GLRaV-2, we report the presence of four groups in Australia. Three of these groups were detected in two plants of cv. Grenache, without finding any recombination event. The hypersensitive reaction of certain American hybrid rootstocks to GLRaV-2 is discussed. Due to the association of GLRaV-2 with graft incompatibility and vine decline, the risk from this virus in regions where hybrid Vitis rootstocks are used cannot be overlooked.